PEMBAGIAN WARIS MENURUT HUKUM ADAT MASYARAKAT SUKU AKIT (STUDI DI KECAMATAN RUPAT UTARA, PULAU RUPAT, KABUPATEN BENGKALIS, PROVINSI RIAU) - YOHANES ORLANDO (PREMISE LAW JURNAL, 2017)
Akitnese adhere to Patrilineal system in which sons play more important roles than daughters regarding inheritance. However, in practice, they distribute their inheritance to their daughters. Inheritance is supposedly given only to sons while daughters do not receive any of it. The research is a judicial empirical research with descriptive analysis using data resources consisting of primary and secondary data. Akitnese is eligible to be categorized into Customary Law Community viewed from physiological and sociological aspects of the existence of the customary law community. However, when observed from judicial point of view, Akitnese has not fully met one of the requirements to be categorized into Customary Law Community as stipulated in the Law No.41/1999 regarding Forestry in conjunction with the Regulations of Ministry of Domestic Affairs No. 52/2014 regarding Orientation for Recognition and Protection of Customary Law Community,namely  regarding the clear law area such as adat land. Inheritance distribution according to Akitnese customary law is held on the seventh day after the inheritor passed away. It is performed in three ways, namely grant (‘peninggal aeh heta’) by the testator during his/her life, through will and testament left for all heirs, and distribution after testator passes away. The efforts to settle the dispute over inheritance distribution for the Akitnese are taken with two ways, namely: a. musyawarah or a meeting leading to consensus (‘hapat/behonding’) among family members and Customary Musyawarah (‘hapat/behonding’).